Motor planning error in Parkinson's disease and its clinical correlates - Kawasaki, Tsubasa (PLoS One, 2018)
This study aimed to investigate (a) motor planning difficulty by using a two-step test in Parkinson’s disease (PD) compared with age-matched healthy subjects and (b) the relationship between motor planning difficulty and clinical factors. The two-step test was performed by 58 patients with PD with Hoehn & Yahr (H&Y) stage I–IV and 110 age-matched healthy older adult controls. In the two-step test, the participants estimated the two-step distance with maximum effort. Subsequently, they performed the actual two-step trial to measure the actual maximum distance. We calculated the accuracy of the estimation (estimated distance minus actual distance). In both groups, subjects who estimated >5 cm were defined as the overestimation group, and those who estimated <5 cm over- and underestimation were defined as the non-overestimation group. The overestimation group consisted of 17 healthy older adults (15.5%) and 23 patients with PD (39.7%). The number of patients with PD with overestimation was significantly more than that of healthy controls by Chi-squared test. H&Y stage and the Unified Parkinson’s Disease Rating Scale (UPDRS) part II and III scores in overestimation group in PD patients were significantly higher than those in overestimation group in PD patients. Moreover, multiple regression using H&Y stage and UPDRS parts II and III as independent variables showed that the UPDRS part II score was the only related factor for the estimation error distance. Estimation error distance was significant correlated with UPDRS parts II and III. Patients with PD easily have higher rates of motor-related overestimation than age-matched healthy controls. In addition, UPDRS parts II and III expressed ability of activities of daily living and motor function as influences on motor-related overestimation. Particularly, multiple regression indicated that UPDRS part II directly showed the ability of daily living as an essential factor for overestimation.